2009
DOI: 10.1158/0008-5472.can-08-2164
|View full text |Cite
|
Sign up to set email alerts
|

A Destructive Cascade Mediated by CCL2 Facilitates Prostate Cancer Growth in Bone

Abstract: Monocyte chemoattractant protein 1 (CCL2) is a recently identified prominent regulator of prostate cancer growth and metastasis. The purpose of this study was to investigate the mechanistic role of CCL2 in prostate cancer growth in bone. The present study found that CCL2 was up-regulated in osteoblasts (3-fold by PC-3 and 2-fold by VCaP conditioned medium) and endothelial cells (2-fold by PC-3 and VCaP conditioned medium). Parathyroid hormone-related protein (PTHrP) treatment of osteoblastic cells up-regulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 28 publications
3
114
0
2
Order By: Relevance
“…Interestingly, when efferocytosis was decreased via incubation at 4°C or neutralizing MFG-E8 antibody treatment, M2 polarization was also reduced, suggesting that efferocytosis is important for macrophage polarization into tumor-promoting M2 cells. When macrophages were challenged with efferocytosis, increased secretion of M2-related cytokines such as IL-6 and CCL-2 (MCP-1) was observed (3,(45)(46)(47). Indeed, the observation that IL-6 is increased dramatically (Ͼ 20-fold) with efferocytosis further supports and explains our findings of STAT3 activation in this pathway.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, when efferocytosis was decreased via incubation at 4°C or neutralizing MFG-E8 antibody treatment, M2 polarization was also reduced, suggesting that efferocytosis is important for macrophage polarization into tumor-promoting M2 cells. When macrophages were challenged with efferocytosis, increased secretion of M2-related cytokines such as IL-6 and CCL-2 (MCP-1) was observed (3,(45)(46)(47). Indeed, the observation that IL-6 is increased dramatically (Ͼ 20-fold) with efferocytosis further supports and explains our findings of STAT3 activation in this pathway.…”
Section: Discussionsupporting
confidence: 82%
“…Tumor-associated macrophages (TAMs) 3 have been investigated in the context of cancer (3,4), but their role in bone metastasis remains elusive (3,5,6). Macrophages are activated differentially according to the stimuli provided.…”
mentioning
confidence: 99%
“…Among these mRNAs are the chemokines Ccl2 and Ccl7 that are implicated in tumor progression. Targeting CCL2 with a neutralizing antibody caused prostate tumor regression (24)(25)(26). The list also includes mRNAs encoding the matrix metalloproteinases (MMPs) MMP3 and MMP9, which are overexpressed in PC3 prostate cancer cells (27), and promote invasion and metastasis by rearrangement of the ECM (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…23,34 Recruitment and differentiation of myeloid cells in tumors are complex processes regulated by multiple pathways, which may lead to differential responses to CSF-1R inhibition. 10,[41][42][43] Several studies have shown that CSF-1/CSF-1R signaling blockade using antibodies or small molecule inhibitors directed against CSF-1R promotes tumor regression, yet the exact mechanism by which this happens is unknown. While some studies have shown that CSF-1R inhibition reduces the number of TAM/myeloid cells, 16,18,23 others have shown that CSF-1R blockade favorably reprograms TAM/myeloid responses without reducing their numbers.…”
Section: Discussionmentioning
confidence: 99%